The Psychology of Nationalism - Searle-White, J. author. aut Link
192 p.
Keywords: Nationalism and other forms of group identity underlie many of the destructive conflicts the world is experiencing today. Particularly puzzling in such conflicts is their tenacity and viciousness. Why do people cling to conflicts that are damaging them? Why are the feelings involved so vehement and intense? Understanding the fragile nature of individual and group identity, and how people perceive threats to identity, can answer these questions. By analyzing nationalism in Quebec, Armenia and Azerbaijan, and Sri Lanka, this book shows that addressing the psychological dimensions of nationalism can help us understand, and perhaps to intervene successfully in, nationalist and ethnic conflicts.